Achieving exceptional strength-ductility synergy in a complex-concentrated alloy via architected heterogeneous grains and nano-sized precipitates. (October 2022) - Fan, Jiantao; Ji, Xinbo; Fu, Liming; Wang, Jian; Ma, Shuo; Sun, Yanle; Wen, Mao; Shan, Aidang
Highlights: A unique heterogeneously-grained structure mixed with L12 nanoprecipitates hardened fine and ultrafine recrystallized grains was tailored in a CO-free Ni42 Fe30 Cr12 Mn8 Al5 Ti3 CCA via a single-step annealing after cold-rolling. The newly-developed CCA featured ultrahigh yield strength and ultimate strength of ∼1.5 GPa and ∼1.8 GPa, respectively, and the product of strength and ductility could reach 32.7 GPa%. The ultrahigh yield strength was mainly attributed to precipitation strengthening, fine-grained strengthening, and extra hetero-deformation induced (HDI) strengthening. Large strain partitioning among heterogeneous domains, leads to strong HDI hardening, which coupled with precipitation hardening and forest dislocation hardening contribute to the exceptional strength-ductility synergy. Abstract: The development of alloys with excellent strength-ductility synergy is a long-lasting research theme for material scientists, which also holds true for the newly emerged complex-concentrated alloys (CCAs). Here, a heterogeneously-grained microstructure consisting of recrystallized ultrafine and fine grains containing dense nano-sized L12 precipitates, which provides synergic strengthening effects, was intentionally introduced into a Co-free CCA through appropriate thermomechanical processing strategy. This CCA exhibits an ultra-high yield strength of 1.5 GPa, a tensile strength of 1.8 GPa and a remarkable uniform elongation of 18.2% at room temperature. During deformation, dislocation-slip is prevalent in fine grains while stacking faults and nanotwins are activated in ultrafine grains. In particular, strain partition takes place and hetero-deformation-induced (HDI) stress is accumulated via pile-ups of massive dislocations at grain boundaries and domain boundaries between fine grain domains and ultrafine grain domains during straining, resulting in significant HDI hardening. This HDI hardening along with the interaction between multiple deformation modes offers the outstanding strain-hardening ability, delaying the onset of necking and hence enabling high strength and good ductility of alloy. Our results indicate that coupling nanoprecipitates with the fully recrystallized heterogeneous grains is an effective strategy to achieve CCAs with advanced strength-ductility balance. Graphical abstract: Image, graphical abstract